2021
DOI: 10.1186/s12981-021-00370-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between antiretroviral therapy-related experiences and mental health status among people living with HIV in China: a prospective observational cohort study

Abstract: Background Mental health problems (e.g., depression and anxiety) are among the most commonly reported comorbidities of HIV. Antiretroviral therapy (ART) coverage has increased sharply. The purposes of this prospective cohort study were to investigate the ART-related experiences and whether they were associated with mental health problems among a sample of people living with HIV undergoing ART in China. Methods The participants were 400 people livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…12,[14][15][16][17][18] In addition, the findings in the current study were similar to the results reported in China, which showed that the level of depression decreased from 23.0% at baseline to 14.0% at month 12 posttreatment. 11 Also consistent with a prospective observational study conducted by Downing et al, 12 the result showed that two sleep quality trajectory groups (bad sleep quality maintained and sleep quality negative change) were highly associated with depression. This suggests that screening for sleep quality and mental health problems is greatly warranted for PLWH who have new HIV diagnoses.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…12,[14][15][16][17][18] In addition, the findings in the current study were similar to the results reported in China, which showed that the level of depression decreased from 23.0% at baseline to 14.0% at month 12 posttreatment. 11 Also consistent with a prospective observational study conducted by Downing et al, 12 the result showed that two sleep quality trajectory groups (bad sleep quality maintained and sleep quality negative change) were highly associated with depression. This suggests that screening for sleep quality and mental health problems is greatly warranted for PLWH who have new HIV diagnoses.…”
Section: Discussionsupporting
confidence: 83%
“… 9 Consecutive care with rolling adjustments based on the patients’ health status and good compliance with ART for PLWH might improve their mental health and sleep quality. 11 However, a recent study observed that after 9 months of follow-up, the sleep quality of most men who have sex with men (MSM) and bisexual men who live with HIV did not change. Only 17% of them improved, and 10% of the subjects have lower sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear, therefore, whether endorsed anhedonia reflects underlying psychological distress or physical manifestations of poor health, whether related to chronic HIV infection or ART side effects. [41][42][43] Future studies should qualitatively elucidate idioms of psychological distress and manifestations of depressive processes in CALWH.…”
Section: Discussionmentioning
confidence: 99%
“…The attitude and knowledge of clinicians ( 15 ), the interface of services between facilities, and limited resources have been reported as external factors affecting ART initiation ( 16 , 17 ). Patients’ personal factors may also contribute to delayed initiation, such as demographic factors including low income, low education, and lack of household decision-making power ( 18 ), HIV-related characteristics ( 14 ), mental health ( 19 , 20 ), and perceptions toward ART ( 21 ). Patients’ willingness to start treatment also influences the decision of ART initiation ( 22 ).…”
Section: Introductionmentioning
confidence: 99%